Socio-Environmental Characterization of Agricultural Production Units in the Ecuadorian Amazon Region, Subjects: Pastaza and Napo - Bravo Medina, Carlos Alfredo (2015)
Through a relative frequency distribution, a group of agricultural production units (APUs) located in the provinces of Pastaza and Napo, Ecuadorian Amazon were socio environmentally characterized. Thirty APUs were selected and a participatory methodology was used that incorporates a set of indicators (25) within the environmental and socio-cultural dimension. From the environmental point of view, the production units are described by having an average size between 21-50 hectares, with 60% of the units studied applying agroecological practices combined with different activities and crops, which reflects the productive potential of the area and how it could serve as a model for the rest of the farms. Soil quality is marked by fine textured clay, with granular structure in the surface horizon, high in organic matter, high acidity, and low fertility, affecting the nutrient availability and limiting its use. Sociocultural characteristics are varied at the farm level, however the evaluation suggests that there are key elements that can affect the continuity and sustainability of the production process, such as: the number of people working in the system, the replacement generation, the aging population, the low management capacity in terms of not keeping records, low institutional support and low participation in governance spaces.